Public Administration in the Field of Using and Protecting Land Resources: International Experience and Ukrainian Realities - V. I. Teremetskyi; H. P. Shust (Law and Safety)
The generalized experience of management in the field of using and protecting land resources in such countries as Denmark, Canada, Latvia, Germany, Poland, the USA, Switzerland, France and others, as well as features of management realization of this sphere in Ukraine have been considered.